2021
DOI: 10.3389/fncir.2021.616084
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Corticomotor Excitability by Repetitive Peripheral Magnetic Stimulation on the Median Nerve in Healthy Subjects

Abstract: Objective: We aimed to examine the effects of repetitive peripheral nerve magnetic stimulation (rPNMS) on the excitability of the contralateral motor cortex and motor function of the upper limb in healthy subjects.Methods: Forty-six healthy subjects were randomly assigned to either a repetitive peripheral nerve magnetic stimulation group (n = 23) or a sham group (n = 23). The repetitive peripheral nerve magnetic stimulation group received stimulation using magnetic pulses at 20 Hz, which were applied on the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Nito et al also demonstrated that a significant increase in MEP was observed up to 60 min following 15 min of 50 or 25 Hz rPMS [41]. Jia, Y et al found that single-session 20 Hz rPMS could modulate corticomotor excitability by measuring MEP, together with a possible lasting improvement in hand dexterity [42]. We observed a 20 min lasting effect of single-session 50 Hz rPMS on implicit body representation of the hand, which is in accordance with the above research.…”
Section: Discussionmentioning
confidence: 99%
“…Nito et al also demonstrated that a significant increase in MEP was observed up to 60 min following 15 min of 50 or 25 Hz rPMS [41]. Jia, Y et al found that single-session 20 Hz rPMS could modulate corticomotor excitability by measuring MEP, together with a possible lasting improvement in hand dexterity [42]. We observed a 20 min lasting effect of single-session 50 Hz rPMS on implicit body representation of the hand, which is in accordance with the above research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that rPMS with single or multiple sessions can significantly reduce spasticity and increase upper limb motor function in patients following central nervous system (CNS) lesions ( 8 10 ). The underlying mechanism might be related to the neuromodulation effect when rPMS is placed over muscle or nerves of the paretic limb ( 9 , 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…It also induces activation of not only the sensorimotor cortex but also the front-parietal network, including premotor and parietal areas [ 1 , 2 ]. In addition, rPMS modulates the corticospinal excitability and intracortical circuits as well as enhances motor performance in healthy individuals [ 3 , 4 , 5 ]. Moreover, rPMS is a novel neurorehabilitation method for improving sensorimotor dysfunctions in stroke [ 1 , 6 , 7 , 8 , 9 , 10 ] and reducing lower back pain [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%